The Sun , 17 Oktober 2007 - Giam, Say Khoon (Sun Media Corp.Sdn.Bhd., 2007)
Under-enrolled Chinese schools, especially in rural areas, need to take in non-Chinese students if they are to remain open, a United Chinese School Teachers Association of Malaysia (Dong Zong) study has found.